Prevalence and predictors of chronic disease among rural and medically underserved populations using smokeless tobacco - Sang, Elaine; Silva, Susan; Grenon, Sarah; Swinkels, Courtney; Shakya, Shamatree; Deshmukh, Salsa; Fish, Laura J.; Da Costa, Mariana; Simmons, Leigh Ann; Severson, Herbert H.; Pollak, Kathryn I.; Noonan, Devon (Frontiers in Public Health, 2025)
IntroductionSmokeless tobacco (SLT) is significant public health problem in the U.S. and is associated with chronic diseases, which includes both physical and mental health conditions. Inequities in use exist as rural and other medically underserved populations use SLT more than that of the general population. Our study examined prevalence of chronic disease and identified associated risk factors among rural and medically underserved populations using smokeless tobacco.MethodsWe conducted a cross-sectional analysis of baseline data (N = 532) from a clinical trial promoting SLT cessation among adults living in rural and/or medically underserved areas and examined the rates of eight chronic diseases: cancer, lung disease, heart disease, stroke, mental health conditions, diabetes, arthritis/orthopedic conditions, and hypertension. Multivariable logistic regression was used to identify risk factors for four of the most common chronic diseases among study participants.ResultsOver 60% of our sample of rural and medically underserved adults who use SLT also have at least one chronic disease. The most common chronic diseases were hypertension (38%), arthritis/orthopedic (23%), mental health (21%), and diabetes (12%). Increasing age and poor/fair health were associated with having hypertension, arthritis/orthopedic conditions, and/or diabetes. In addition, drinking alcohol <5 days per week was associated with having diabetes. Meanwhile, greater nicotine dependence, marital status, and having stained teeth were associated with having a mental health condition.ConclusionsFindings may inform the development of SLT cessation interventions as part of broader chronic disease management programs and as part of secondary prevention to minimize tobacco related morbidity.